2013
DOI: 10.1002/ijc.28344
|View full text |Cite
|
Sign up to set email alerts
|

Neglected role of hookah and opium in gastric carcinogenesis: A cohort study on risk factors and attributable fractions

Abstract: A recent study showed an association between hookah/opium use and gastric cancer but no study has investigated the relationships with gastric precancerous lesions. We examined the association between hookah/opium and gastric precancerous lesions and subsequent gastric cancer. In a population-based cohort study, 928 randomly selected, healthy, Helicobacter pylori infected subjects in Ardabil Province, Iran, were followed for 10 years. The association between baseline precancerous lesions and lifestyle risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 33 publications
5
68
0
Order By: Relevance
“…Our findings are consistent with the result of hookah smoking in a previous Iranian study [7]. This Iranian cohort study reported more than three-fold higher GC risk in hookah smokers (relative risk = 3.4, 95%CI = 1.7–7.1) even after adjusting for the effects of other confounding factors, which might be because of the high-risk study population, namely H .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with the result of hookah smoking in a previous Iranian study [7]. This Iranian cohort study reported more than three-fold higher GC risk in hookah smokers (relative risk = 3.4, 95%CI = 1.7–7.1) even after adjusting for the effects of other confounding factors, which might be because of the high-risk study population, namely H .…”
Section: Discussionsupporting
confidence: 92%
“…The Iranian study [7] also reported a significant increase of GC risk by cigarette smoking (relative risk = 3.2, 95%CI = 1.4–7.5) as reported in previous studies [24]. However, our study did not find the association between cigarette smoking and GC risk.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…While studies vary, overall the accumulated data suggest that smoking is a risk factor for both cardia and noncardia GC (33-35). Other forms of tobacco use, such as hookah use, have also been associated with higher risk of GC (36), although these associations have not been found in other studies (37) and need further confirmation.…”
Section: Demographic and Environmental Risk Factorsmentioning
confidence: 89%
“…Among these risk factors are poor oral hygiene and tooth loss (37, 113, 114), opium use (36, 115-117), infection with Ebstein-Barr virus (118, 119), and eating pickled vegetables (120). …”
Section: Demographic and Environmental Risk Factorsmentioning
confidence: 99%